Políticas de memoria y transmisión: apuntes para analizar la relación entre dispositivos de mediación y visitantes en espacios de memoria (Argentina) - Agustina Cinto (Nuevo mundo - Mundos Nuevos, 2024)
The article contributes to the analysis of the relationship between memorial mediation devices and visitors in spaces of memory in Argentina, an area where local analytical development is still limited. Considering that there is a process of co-constitution between the devices and the visitors during the visit experience, the transmission occurs and is the product of this encounter. Therefore, this analysis finds precedents in memory studies focused on recovered former clandestine detention centers, adding insights from studies on audiences or visitors, primarily conducted in museum institutions. First, we establish some theoretical-methodological keys to study transmission in these particular spaces, considering that it has been one of the main objectives of the politics of memory implemented there. Second, we comparatively address three Argentinian spaces of memory where transmission has been analyzed, considering their devices, predominant narratives, and the visitors' perspective. We hypothesize there is no direct correspondence between the meanings proposed by the devices and what is transmitted to the visitors. Far from the transfer of a homogeneous narrative about recent history, transmission in these spaces ranges from generating empathy for the events to questioning them.